A comparative study of Mn/Co binary metal catalysts supported on two commercial diatomaceous earths for oxidation of benzene - Tomatis, Marco; Xu, Honghui; Wei, Chaohui; Bishop, Matthew Thomas; He, Jun; Wang, Chengjun; Zhao, Ming; Xiao, Hang; Yu, Huan; Behera, Sailesh N.; Tang, Bencan (MDPI, 2018)
Two commercial diatomaceous earths were used as supports for the preparation of Mn/Cobinary metal catalysts at different metal loads (5 to 10 wt % Mn and 5 to 15 wt % Co) by incipientwetness deposition. The activity of the prepared catalysts towards the complete oxidation of benzeneto CO2and water was investigated between 100 and 400◦C. Raw supports and synthesized catalystswere characterized by XRD, N2physisorption, SEM-EDS, H2-TPR, and TPD. The purificationtreatment of food-grade diatomite significantly affected the crystallinity of this support whilereducing its specific surface area (SSA). A loss of SSA, associated with the increase in the metalload, was observed on samples prepared on natural diatomite, while the opposite trend occurredwith food-grade diatomite-supported catalysts. Metal nanoparticles of around 50 nm diameter wereobserved on the catalysts’ surface by SEM analysis. EDS analysis confirmed the uniform depositionof the active phases on the support’s surface. A larger H2consumption was found by TPR analysisof natural diatomite-based samples in comparison to those prepared at the same metal load onfood-grade diatomite. During the catalytic oxidation experiment, over 90% conversion of benzenewere achieved at a reaction temperature of 225◦C by all of the prepared samples. In addition, theformation of coke during the oxidation tests was demonstrated by TGA analysis and the solublefraction of the produced coke was characterized by GC-MS.